Microbial attenuation of atrazine in agricultural soils: Biometer assays, bacterial taxonomic diversity, and catabolic genes. (June 2017) - Douglass, James F.; Radosevich, Mark; Tuovinen, Olli H.
Abstract: The purpose of this study was to examine the potential biomineralization of atrazine and identification of atrazine-degrading bacteria in agricultural soils. Different atrazine application histories of soils impacted the kinetics of biomineralization but not the presence of catabolic genes of two atrazine degradative pathways (Trz and Atz). Biomineralization was based on the measurement of 14 CO2 from [U-ring- 14 C]-atrazine in surface soil (0–7 cm) samples incubated in biometers. Aerobic atrazine biomineralization rate constants ( k ) varied in the range of 0.004–0.508 d −1 depending on the specific soil sample and glucose amendment. The corresponding k -values for anaerobic biometers ± nitrate, ferrihydrite or sulfate were 0.002–0.360 d −1 . Glucose enhancement of atrazine biomineralization was not consistent. Aerobic enrichments from soil samples and in-situ incubated BioSep beads yielded mixed cultures, four of which were characterized by 16S rRNA gene amplification, cloning and sequencing. Twelve pure cultures were isolated from enrichments and they were primarily Arthrobacter spp. (10/12). The presence of eight atrazine catabolic genes representing two degradative pathways was investigated in seven bacterial isolates by PCR amplification and sequencing. Several combinations of atrazine catabolic genes were detected; each contained at least atzBC . A complete set of genes for the Atz pathway was not found among the isolates. Our data indicate that atrazine metabolism involves multiple microorganisms and cooperative pathways diverging from atrazine metabolites. Graphical abstract: Highlights: [Ring-U- 14 C]-atrazine biomineralization in soil samples was tested in biometers. Atrazine-degrading cultures were obtained by enrichment of soil borne bacteria. Bacteria isolated from enrichment cultures were mostly Arthrobacter spp. Atz and Trz pathway catabolic genes were screened in bacterial isolates. Genes of Atz and Trz pathways were found in isolates but not as complete sets.